2014
DOI: 10.9734/ca/2014/9731
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Diseases and Associated Risk Factors in WHO Eastern Mediterranean Countries

Abstract: Background: In the WHO Eastern Mediterranean region, nearly one million deaths are caused by cardio-vascular diseases every year. During the last decade, the number of deaths caused by stroke increased by 23%. Most cardiovascular diseases can be prevented by addressing behavioural risk factors such as tobacco use, alcohol, unhealthy diet, physical inactivity, and metabolic risk factors like obesity, high blood pressure, diabetes and raised lipids. Methods: This is a systematic review on cerebrovascular disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
(140 reference statements)
6
10
0
Order By: Relevance
“…Which joins the results of the literature review of studies conducted in the Middle East between 1980 and 2015, showing that HBP was the most common risk factor, followed by diabetes [52]. These findings are also consistent with data collected in the Eastern Mediterranean countries, where the prevalence of HBP was above 50% in 38 studies, diabetes percentage was higher than 25% in 36 studies, and smoking was higher than 15% in 26 studies [51].…”
Section: The Percentage Of Patients With Thrombolyzed Ischemic Strokesupporting
confidence: 88%
“…Which joins the results of the literature review of studies conducted in the Middle East between 1980 and 2015, showing that HBP was the most common risk factor, followed by diabetes [52]. These findings are also consistent with data collected in the Eastern Mediterranean countries, where the prevalence of HBP was above 50% in 38 studies, diabetes percentage was higher than 25% in 36 studies, and smoking was higher than 15% in 26 studies [51].…”
Section: The Percentage Of Patients With Thrombolyzed Ischemic Strokesupporting
confidence: 88%
“…Hypertension and diabetes mellitus are major clinical and public health problem in Kingdom of Saudi Arabia and the Middle East28,29,30 ) . The findings of this study showed also a high proportion of recurrent stroke patients had both of them as coexistent risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…is section deals with the numerical methods used in this paper without restrictions of the time interval. In the beginning, we intend to solve model (1) in the absence of control u by the following discrete method, which offers accurate solutions during a long time interval.…”
Section: Description Of the Numerical Methodsmentioning
confidence: 99%
“…However, some people may need to take medications after undergoing medical procedures. CHD can be prevented by addressing risk factors, which is divided into uncontrollable risk: gender (in middle age, common in males than females due to estrogen protective effect, but after menopause, the percentage will be equal), age (incidence increases by age), congenital predisposition (positive family history), and controllable risk: metabolic risk factors such as hypertension, diabetes, obesity, and dyslipidemia (the most common forms of dyslipidemia involve high levels of low-density lipoproteins (LDL) or bad cholesterol and low levels of high-density lipoproteins (HDL) or good cholesterol), and behavioural risk factors such as smoking, alcohol, physical inactivity, and unhealthy diet (see for details [1]).…”
Section: Introductionmentioning
confidence: 99%